A new genus and species of Collembola from caves of south Iberian Peninsula (Collembola, Poduromorpha, Onychiuridae) - Martínez, Maite; Baquero, Enrique; Barranco, Pablo; Ariño, Arturo H.; Jordana, Rafael (Zootaxa, 2004)
A new genus and species of Onychiuridae (Collembola, Poduromorpha) from caves in the south of the Iberian Peninsula is described. The usual dichotomous keys would locate this species somewhere between the genera Protaphorura Absolon and Heteronychiurus Bagnall. The new genus has four rows of setae on abdominal tergite VI, rudimentary furca as a cuticular fold and an anterior granulated area, 2+2 dorsal pseudocelli on the posterior part of the head, 1+1 dorsal pseudocelli on thoracic tergite I, 2+2 dorsal pseudocelli on abdominal tergite V, 1+1 pseudopores in each thoracic sternite, and the microsensillum on the basal part of the apical third of the antennal segment IV.